2016
DOI: 10.5539/ass.v12n8p104
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Loneliness and Cognitive Distortion among Young Unwed Pregnant Women in Malaysia: Counseling Implications

Abstract: Inability to meet the demands and challenges resulting from the rapid social and economic growth bring about social and psychological problems among youths and their families. One of the problems that young women are facing now is unwed pregnancies. Unwed pregnancies bring about negative social and psychological effects. The objective of this quantitative study is to ascertain the relationships among depression, loneliness and cognitive distortion. Respondents for this study were 150 young unwed pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…At the same time, the explanation of loneliness as unsatisfactory rather than the frequency of social relationships shows us the relationship between cognitive distortions and loneliness [41]. Therefore, some studies have felt the need to focus on cognitive aspects to explain loneliness [79]. In particular, Hamamcı and Duy found that cognitive distortions related to avoiding intimacy have a negative effect on the experience of loneliness [80].…”
Section: The Relationship Between Interpersonal Cognitive Distortions Loneliness and Satisfaction With Lifementioning
confidence: 99%
“…At the same time, the explanation of loneliness as unsatisfactory rather than the frequency of social relationships shows us the relationship between cognitive distortions and loneliness [41]. Therefore, some studies have felt the need to focus on cognitive aspects to explain loneliness [79]. In particular, Hamamcı and Duy found that cognitive distortions related to avoiding intimacy have a negative effect on the experience of loneliness [80].…”
Section: The Relationship Between Interpersonal Cognitive Distortions Loneliness and Satisfaction With Lifementioning
confidence: 99%
“…[52] We note that after 1996, some published studies had a lack of clarity about which version of the UCLA Scale was used. For example, beginning in 1998 and continuing through 2016, six articles [19,23,24,27,30,58] report the use of the 20-item Revised UCLA Loneliness Scale, and often cite Russell et al (1980), despite Version 3 being the most up-to-date version.…”
Section: Measurements Of Loneliness Usedmentioning
confidence: 99%
“…loneliness was found to have a direct negative effect on postpartum depression and infantmother bonding;[89] and c.) loneliness was positively correlated with postpartum depression. [30] A pattern of loneliness experienced in postpartum depression included the common belief that others did not understand the mothers' experiences of depression,[82-85, 87] and a sense that attempts to communicate struggles with depression were unsuccessful. [82, 84, 85] These perceptions resulted in mothers feeling alienated from their relations; consequently, mothers isolated themselves from their support network.…”
Section: Factors Associated With Loneliness In Mothers and Fathers Collectivelymentioning
confidence: 99%
“…Despite extensive loneliness research primarily addressing the elderly and/or other high-risk groups across the lifespan, parents and pregnant people, as a group, remain an underrepresented population within loneliness studies [1], and few studies of new parents have made the examination of loneliness a primary aim (see exceptions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]). There is a gap, therefore, in our understanding of the psychosocial needs and health risks of loneliness in pregnant persons and new parents.…”
Section: Introductionmentioning
confidence: 99%